A study of chemically reactive species and thermal radiation effects on an unsteady MHD free convection flow through a porous medium past a flat plate with ramped wall temperature - Pandit, Kamalesh; Sarma, Debojit; Singh, S.J. (Zielona Góra: Uniwersytet Zielonogórski)
An investigation of the effects of a chemical reaction and thermal radiation on unsteady MHD free convection heat and mass transfer flow of an electrically conducting, viscous, incompressible fluid past a vertical infinite flat plate embedded in a porous medium is carried out. The flow is induced by a general time-dependent movement of the vertical plate, and the cases of ramped temperature and isothermal plates are studied.
Keywords: free convection; chemical reaction; thermal radiation; MHD; porous medium; ramped temperature